Sex, Skulls, and Citizens : Gender and Racial Science in Argentina (1860-1910) - Kerr, Ashley Elizabeth, 1984- (Book collections on Project MUSE., 2020)
"Based on analysis of a wide variety of late-nineteenth-century sources, this book argues that indigenous and white women shaped Argentine scientific racism as well as its application to projects aiming to create a white, civilized nation. The writers studied here, scientists, anthropologists, and novelists, including Estanislao Zeballos, Lucio and Eduarda Mansilla, Ramon Lista, and Florence Dixie, reflect on indigenous sexual practices, analyze the advisability and effects of interracial sex, and use the language of desire to narrate encounters with indigenous peoples as they try to scientifically pinpoint Argentina's racial identity and future potential"--